2012
DOI: 10.1182/blood.v120.21.165.165
|View full text |Cite
|
Sign up to set email alerts
|

Early Molecular Response and Female Sex Strongly Predict Achievement of Stable Undetectable BCR-ABL1, a Criterion for Imatinib Discontinuation in Patients with CML

Abstract: 165 Introduction. The opportunity to discontinue kinase inhibitor therapy while maintaining a deep remission is desirable for many CML patients. Despite good responses to imatinib for most patients, treatment related side effects remain problematic and can affect quality of life. Studies have demonstrated that a proportion of carefully selected patients can sustain response after imatinib discontinuation. The first requirement for successful discontinuation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Univariate analysis of a study in patients treated with first-line imatinib showed that females were more likely than males to achieve stable undetectable BCR-ABL1 (with a RQ-PCR sensitivity of !4.5 log) by 8 years (68% vs. 30%, respectively; ref. 50). Multivariate analysis of a study in Japanese patients found adherence to standard-dose imatinib to be predictive of CMR achievement (51).…”
Section: Factors Affecting Achievement Of Deep Molecular Responsementioning
confidence: 99%
“…Univariate analysis of a study in patients treated with first-line imatinib showed that females were more likely than males to achieve stable undetectable BCR-ABL1 (with a RQ-PCR sensitivity of !4.5 log) by 8 years (68% vs. 30%, respectively; ref. 50). Multivariate analysis of a study in Japanese patients found adherence to standard-dose imatinib to be predictive of CMR achievement (51).…”
Section: Factors Affecting Achievement Of Deep Molecular Responsementioning
confidence: 99%